KEABSAHAN PERJANJIANiJUALiBELIsDENGANiHAKiMEMBELI KEMBALIiATAS TANAH DAN BANGUNAN (STUDIsKASUS: PUTUSAN NOMOR 672/PEN/PDT/2017/PT.DKI JO. 359/PDT.G/2016/PN.JKT.UTR.) - Fernando Fernando; Gunawan Djajaputra (Jurnal Hukum Adigama, 2019)
The agreement is something that often happens in the community. In the making of agreement, ittis necessaryytoyknowythatythereyare conditions for the agreement to be valid, theelegaletermseofetheeagreement are stipulated in articlee1320eof IndonesiansCivillCode, spesifically agreeing, capable, certain matters and legal causes. in thersale sanddpurchase agreementewithetheerighttto repurchase land, it gives the seller a power to repurchase the land that he sold, but this is not known in the Basic Agrarian Law No. 5/1960, where in the Agrarian Law is based on customary law which adheres to a system of Clear, Cash and Real. So that in this case it gives legal uncertainty, but because the Book III of Indonesia Civil Code adheres to an open system where it can be ascertained from the principle of freedom of contract then theesaleeandepurchaseeagreementewithethe right toerepurchases valid, but the purchase and repurchase rights will become null and void if viewed from the side of the Basic Agrarian Law, so that the sale and purchase agreement with the right to repurchase in Indonesian Civil Code with the Basic Agrarian Law must be clearly separated. So if there is a dispute in it, accordance with jurisprudences regarding the sale and purchase agreement with the right to repurchase, where the purchase agreement with the right to repurchase land is absolutely null and void and becomes a debt agreement with land guarantee.